Mengapa Olahraga Penting? Peran Pendidikan Jasmani, Olahraga, dan Kesehatan (PJOK) di Sekolah Dasar - Mulyana, Agus; An-Nazwa, Fatimah; Amanatin, Ifah; Afifah, Linda Dwi Ayuni; Handayani, Shinta Risma; Zikri, Shiva Aqila; Wati, Talitha Arista (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The main objectives of PJOK include increasing physical potential, cultivating sportsmanship characters, and awareness of healthy living, which is achieved through various activities and physical activities. This study uses a literature review. Literature search for commonly used journal sources in Indonesia. Selected articles must meet the inclusion criteria, i.e. published between 2015 and 2024. Information from selected articles is thoroughly analyzed through abstract sections, methods, and results. After data collection, analysis is performed by narrative synthesis method to combine findings from various studies. The results of the study show that PJOK in elementary schools serves as the main foundation in forming healthy living habits and children's character from an early age. Structured physical activity through PJOK helps develop motor skills, an understanding of the importance of nutrition, and healthy living habits. In addition to physical benefits, PJOK also plays an important role in developing children's character, such as discipline, responsibility, cooperation, and leadership. Sport has a broad positive impact, covering the physical, mental, and social aspects of children, helping them manage stress, improve cognitive function, and develop social skills. PJOK contributes significantly in creating a generation that is healthy, accomplished, and charactered, through the integration of affective values in every learning activity.